2001
DOI: 10.1094/cchem.2001.78.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Milling Effects on Rice Pasting Properties

Abstract: The effects of degree of milling on pasting properties of medium‐grain (cv. Bengal and Orion) and long‐grain rice (cv. Cypress and Kaybonnet) were quantified using a Brabender ViscoAmylograph and a Rapid Visco Analyser. For all the cultivars tested, surface and total lipid contents decreased as the degree of milling increased. The peak viscosities for all rice increased with the degree of milling and the rates of increase were higher for medium‐grain than long‐grain cultivars. Degree of milling did not have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 5 publications
8
64
0
Order By: Relevance
“…Majority of cultivars showed a decrease in FV also with N application at higher level of N application. The decreases in PV and FV with increasing N application may be due to a combination of increase in protein content as well surface lipids content as previously reported (Martin and Fitzgerald 2002;Perdon et al 2001). BDV and SBV showed positive correlation with AAC (Table 4).…”
Section: Pasting Propertiessupporting
confidence: 79%
“…Majority of cultivars showed a decrease in FV also with N application at higher level of N application. The decreases in PV and FV with increasing N application may be due to a combination of increase in protein content as well surface lipids content as previously reported (Martin and Fitzgerald 2002;Perdon et al 2001). BDV and SBV showed positive correlation with AAC (Table 4).…”
Section: Pasting Propertiessupporting
confidence: 79%
“…However, samples milled for the same duration to various milled rice temperatures were not significantly different (P >0.05) ( Table 1). This was critical in our case since degree of milling is known to significantly affect rice functional properties (Saleh and Meullenet 2007;Perdon et al 2001). Table 1 also shows the effect of rice milling to various temperatures on HRY.…”
Section: Milled Rice Quality Characteristicsmentioning
confidence: 99%
“…High trough indicates a tendency of the rice starch to break down during cooking; thus, trough values usually decrease with cooking (Danbaba et al 2012). Removal of bran in the milling process reduces the amylase content of rice and thereby results in less active amylase and higher trough viscosity (Perdon et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Parboiling is a hydrothermal process consisting of soaking, heating and drying operations that modify the qualitative parameters and processing behaviour of rice (Mir & Bosco 2013). Numerous studies have shown that processing conditions affect the functionality and quality of the final rice product (Hamaker et al 1993;Perdon et al 2001). Zhou et al (2002) revealed that one of the sensitive indices of the ageing process in rice is the change in pasting properties, which is dependent on storage temperature and duration.…”
mentioning
confidence: 99%